(untitled) (Nexus International Journal of Science and Education, 2024)
The study determined the extent of teachers' facilitation skills of learning standards and its association with learners' adaptability across disciplines in Marilog A District, Davao City Schools Division. The study used a non-experimental descriptive-correlational research design, where it utilized an adapted survey instrument to gather responses from the 80 randomly selected teacher-respondents. Data gathered were treated using Mean scores with descriptive interpretation, Pearson r, and Simple Linear Regression Analysis. Findings revealed that teachers’ facilitation skills of learning standards in terms of differentiated instruction, assessment and evaluation, classroom management, and pedagogical content knowledge were moderately extensive, as well as learners' adaptability across the discipline in terms of pronunciation, reading comprehension, writing skills, vocabulary, grammar and speaking and listening. There was a significant relationship between teachers' facilitation skills of learning standards and learners' adaptability across disciplines. Domains of teachers' facilitation skills of learning standards in terms of pedagogical content knowledge, differentiated instruction, assessment and evaluation, and classroom management suggest significant influence over learners' adaptability across the disciplines. Future research may investigate the impact of professional development programs on teachers' facilitation skills and their influence on learners' adaptability. Identify effective models of professional development that support teachers in enhancing their instructional practices and promoting adaptability across disciplines. Investigate the Relationship between a school's culture, including leadership support, collaboration, a focus on differentiation and interdisciplinary learning, and students' adaptability across disciplines.